Preparation, Characterization And Adsorption Studies Of Clay And Chitosan-Based Composite Adsorbents For Acid, Basic And Reactive Dyes - Auta, Manase (2013)
Potentials of abundant renewable waste and mineral resources in Malaysia were harnessed for preparation of adsorbents for adsorption of dyes from synthetic wastewaters. Optimized waste tea activated carbon (WTAC) and paper sludge activated carbon (PSLG) were prepared using potassium fluoride and acetate as new activating agents while other adsorbents were prepared from dolomite, Ipoh, Ball and Kuala Kangsar clays through calcinations and modification with aluminum hydroxide and sulphuric acid. The variables optimized were activation temperature and time, chemical impregnation ratio; and the responses were yield and dye adsorption. The optimal conditions for WTAC were 1.4:1 impregnation ratio (IR), 120 min and 800 oC while 0.95 IR, 105 min and 810 oC were obtained for PSLG. The adsorbents were characterized for BET surface area analysis, scanning electron microscopy, Fourier transform infrared, elemental analysis and X-ray fluorescence to determine their physical and chemical characteristics. The BET surface area of 2.97-854.25 m2/g and porosity of 0.003-0.516 cm3/g were obtained. A range of 30-350 mg/L, 30-50 oC and pH 2-12 were used to study the effect of initial concentration, process temperature and pH on the batch adsorption experiments. The effect of initial dye concentration, bed height and flow rate on breakthrough curves in fixed-bed column adsorption were investigated.